2018
DOI: 10.1002/ange.201802397
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Formation of (E)‐β‐Vinylstannanes with a Topologically Controlled Molybdenum‐Based Alkyne Hydrostannation Catalyst

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Furthermore, 1 H‐coupled, 31 P NMR spectroscopic analysis of the reaction mixture revealed one singlet resonance centered at δ =+105 ppm. This chemical shift is within the range found for complexes 1 and 2 ( δ =+90 and +60 ppm for 1 ; δ =+113 ppm for 2 ), which suggested that the cyclo ‐P 4 ligand remained intact upon treatment of 1 with KC 8 . Notably, FTIR spectroscopy of this product in C 6 D 6 solution revealed an asymmetric set of broad, low‐energy ν CN and ν CO bands (1900–1650 cm −1 ) consistent with both a highly reduced metal center and contact ion pairing between the complex and potassium ions .…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, 1 H‐coupled, 31 P NMR spectroscopic analysis of the reaction mixture revealed one singlet resonance centered at δ =+105 ppm. This chemical shift is within the range found for complexes 1 and 2 ( δ =+90 and +60 ppm for 1 ; δ =+113 ppm for 2 ), which suggested that the cyclo ‐P 4 ligand remained intact upon treatment of 1 with KC 8 . Notably, FTIR spectroscopy of this product in C 6 D 6 solution revealed an asymmetric set of broad, low‐energy ν CN and ν CO bands (1900–1650 cm −1 ) consistent with both a highly reduced metal center and contact ion pairing between the complex and potassium ions .…”
Section: Methodssupporting
confidence: 73%
“…For example, there is a remarkable consistency in average P−P bond distances across the series. For [K 2 (db18‐c‐6)][ 3 ] and K 2 [ 4 ], these average distances are identical and are essentially the same as complexes 1 and 2 (Table ) . This similarity strongly suggests that the cyclo ‐P 4 units of these complexes have a common electronic structure, irrespective of the valency of these molybdenum centers.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Very recently, a molybdenum-based pre-catalyst system (MoI2-(CO)2(CNAr Dipp2 )2 51; (Ar Dipp2 )= 2,6-(2,6-(i-Pr)2C6H3)C6H3 featuring two encumbering m-terphenyl isocyanides ligands was used to deliver (E)--vinylstannanes with an excellent regioselectivity from a variety of terminal and internal alkynes (Scheme 61). 126 Under the conditions depicted in Scheme 61, Pre-catalyst 51 converts phenylacetylene into the corresponding (E)--vinylstanne with an excellent regioselectivity (: = 87/13) which is markedly superior to that of classical Pd catalysts as PdCl2(PPh3)2 and Pd(PPh3)4; (: = 54/46) and (: = 50/40), respectively. 16 Terminal aryl alkynes having electronrich substituents (e.g.…”
Section: Scheme 60 Mo-catalyzed Hydrostannation Of Chloro and Amino mentioning
confidence: 99%
“…Nevertheless, the process involves a complex fabrication process and generation of toxic white phosphorus, which makes it unsuitable for actual production. 33 On the other hand, p-type doping in graphene is able to increase the work function of the system due to the charge transfer from graphene to p-dopant adatoms. 34 We believe that appropriate control of the work function can reduce the formation of the SEI film because the electron charge depletion on the surface may hinder the reduction of electrolytes, which is actually the starting point of this study.…”
Section: Introductionmentioning
confidence: 99%